Negative refraction metamaterial with low loss property at millimeter wave spectrum - B. A. F. Esmail; H. A. Majid; F. A. Saparudin; M. Jusoh; A. Y. Ashyap; Najib Al-Fadhali; M. K. A. Rahim (Institute of Advanced Engineering and Science, 2020)
The design of the millimeter-wave (MMW) metamaterials (MMs) unit cell operates at 28 GHz is presented and numerically investigated. The proposed structure composed of a modified split ring resonator (MSRR) printed on both sides of the substrate layer. Popular MM structures such as S-shape, G-shape, and Ω-shape are adjusted to operate at the 28 GHz for comparison purpose. MSRR achieves a wide bandwidth of 1.1 GHz in comparison with its counterparts at the resonance frequency. Moreover, the proposed structure presents very low losses by providing the highest transmission coefficient, S21, at the corresponding frequency region. The radiation loss is substantially suppressed and the negativity of the constitutive parameters of the proposed MM structure is maintained. By applying the principle of the electromagnetically induced transparency (EIT) phenomenon, the MSRR unit cell induces opposite currents on both sides of the substrate which leads to canceling out the scattering fields and suppresses the radiation loss. The constitutive parameters of the MM structures are retrieved using well known retrieval algorithm. The proposed structure can be used to enhance the performance of fifth generation (5G) antenna such as the gain and bandwidth.